The “puberty deadline”: cultural constructions of maturity, anticipated shame, and child marriage as a perceived risk-mitigation strategy in rural Niger - Jean Christophe Fotso; Aichatou Hamadou; Ferdinard Ngong; Paul Bukuluki (Frontiers in Reproductive Health, 2026)
Introduction In rural Niger, child marriage remains highly prevalent, often functioning as a mechanism of risk mitigation. This qualitative study explores the cultural and bio-social drivers of child marriage, focusing on the intersection of physical maturation, anticipatory shame, and economic vulnerability. Methods The study drew on 53 in-depth interviews, six body mapping focus group discussions (FGDs), and 9 social norms mapping FGDs with adolescents, parents, and community leaders (n = 165) in the Maradi region. Results We find that participants perceive the biological onset of menarche as a ‘puberty deadline.’ This biological trigger socially reclassifies girls from children to women perceived to be vulnerable, sparking acute parental anxiety over premarital sexuality and the stigma of out-of-wedlock pregnancy. Conversely, the reported covert use of contraceptives by some adolescent girls, sometimes with maternal complicity, serves to protect reputations while delaying marriage, highlighting complex implications for adolescent autonomy and consent. Discussion Our findings highlight a stark gender asymmetry in the transition to adulthood and demonstrate that child marriage in this context is perceived to be driven by the dual pressures of moral safeguarding and poverty. Implications for future interventions include addressing both the gendered cultural narratives of maturity and the underlying economic desperation sustaining the practice, which may be essential for achieving lasting change.